Investigations on pressure dependence of Coriolis Mass Flow Meters used at Hydrogen Refueling Stations. (December 2020) - Büker, Oliver; Stolt, Krister; de Huu, Marc; MacDonald, Marc; Maury, Rémy
Abstract: In the framework of the ongoing EMPIR JRP 16ENG01 "Metrology for Hydrogen Vehicles" a main task is to investigate the influence of pressure on the measurement accuracy of Coriolis Mass Flow Meters (CFM) used at Hydrogen Refueling Stations (HRS). At a HRS hydrogen is transferred at very high and changing pressures with simultaneously varying flow rates and temperatures. It is clearly very difficult for CFMs to achieve the current legal requirements with respect to mass flow measurement accuracy at these measurement conditions. As a result of the very dynamic filling process it was observed that the accuracy of mass flow measurement at different pressure ranges is not sufficient. At higher pressures it was found that particularly short refueling times cause significant measurement deviations. On this background it may be concluded that pressure has a great impact on the accuracy of mass flow measurement. To gain a deeper understanding of this matter RISE has built a unique high-pressure test facility. With the aid of this newly developed test rig it is possible to calibrate CFMs over a wide pressure and flow range with water or base oils as test medium. The test rig allows calibration measurements under the conditions prevailing at a 70 MPa HRS regarding mass flows (up to 3.6 kg min −1 ) and pressures (up to 87.5 MPa). Highlights: A unique high-pressure flow test facility has been concepted and built. The test rig allows measurements under conditions prevailing at 70 MPa HRS. Traceable measurements allow separation of pressure and temperature effects. Five high-pressure CFMs from three leading manufacturers have been investigated.